Bevin blocks aid for Spain (press cutting)
022_0007-001 NEWSPAPER CUTTINGS Subject Reference Daily Worker, 12.3.37 Sheet No. Folder No. BEVIN BLOCKS AID FOR SPAIN DELEGATES SHOCKED AT "BRUTAL" DECLARATION Spaniards Repudiate Shameful Betrayal SHARP DIVISIONS REVEALED AT WORLD CONFERENCE (From a Special Correspondent) WESTMINSTER, Thursday. ERNEST BEVIN declared himself to be speaking in the name of the whole British Labour movement when he flatly told the Spanish delegation and their mass of international supporters in the International Conference today that the British Labour movement absolutely refused to accede to their most urgent demands for international action to save Spain's democracy and the peace of the world. His speech was described by Vandervelde, Belgium's Socialist leader, as " brutal " and as a " cold douche " thrown on the hopes of effective action for Spain. THE CHARACTER OF BEVIN'S SPEECH MAY BE JUDGED FROM THE FACT THAT THE SPANISH DELEGATION, WHO, UP TO THE LAST MOMENT, HAD BEEN HOPING THAT HIS SPEECH WOULD INDICATE THAT THE LEADERS OF THE BRITISH LABOUR MOVEMENT WERE NOT AFTER ALL GOING UTTERLY TO DESERT THE CAUSE OF DEMOCRACY, DECIDED IMMEDIATELY THE SPEECH WAS OVER TO REFUSE TO PARTICIPATE IN THE CONFERENCE COMMISSION ON THE GROUNDS THAT THEY COULD NOT ASSOCIATE THEMSELVES WITH A BODY WHOSE POLICY SEEMED LIKELY TO BE DOMINATED BY THE DESTRUCTIVE AND DISRUPTIVE DEMANDS OF THE BRITISH DELEGATION. Instead, they presented to the Commission a statement, embodying once again their own clear-cut demands for action. No wonder that following Bevin's speech, Vandervelde revealed that while the Spaniards had told him in conversation they were sure of the ultimate loyalty of the Belgians, Dutch and Scandinavians, it was the British Labour Party and the British trade union leadership they had feared all along would desert them. Vandervelde repeated openly yesterday afternoon a statement I already heard whispered in the corridors of the Congress. "This," he said, " is the turning point in the history of the Second International. From this Conference will result either dissolution of the Second International, or a new departure for a more glorious future." He made no secret of his belief now already expressed on the previous evening by Pietro Nenni in the name of the Italian delegation - that if Bevin's policy in fact prevails, this is the death rattle of the Second International. One-third of Bevin's speech was devoted to an attack on the Communists, and on the idea of national and international unity. He declared, among other things, that the L.C.C. elections had been won in spite of the Communists. He said that the fact of the war in Spain must not be allowed at any cost to influence the decisions and the policy of the British Labour leaders in this country. He boasted at intervals of the great things done for Spain by British Labour, but when he came to facts was only able to speak of "diplomatic pressure" behind the scenes and Parliamentary resolutions. He actually defended the National Government on the grounds that we had Eden's word for it that no pressure had been brought by the Conservative British Government on the Blum Government last August in order to pursuade the French Government to refuse arms to the legal Government of Spain. DELEGATE'S VIEW A delegate who listened to the whole of Bevin's speech told me he doubted whether Transport House would ever dare to make it public. The only point at which Bevin approached the essential demand at all was on the question of foreign troops and volunteers fighting in Spain. He stated that the British public would, he thought, be in favour of the withdrawal of these forces, provided that the anti-fascist volunteers fighting in the International Brigades were treated on the same footing as the German and Italian troops, the Portuguese and the Moors. He refrained, however, from suggesting any practical pressure by which this could be applied, and particularly avoided the proposal of strike action to enforce this demand, which was not only made by the Spanish delegation but had a few minutes before received the full support of Leon Jouhaux, leader of the French T.U.C. Bevin was far from recognising the monstrous character of the proposed naval control with which, in the words of Vandervelde, the aggressors are put in control of the very country they are attacking, confining himself to stating that the control would not be efficacious unless some form of supervision was set up by the International, and sought to comfort the Spaniards that if the control was proved ineffective the British Labour Party would " bombard the Government with protests." FRENCH DECLARATION The chill and the utter disappointment which followed Bevin's speech hung over the Conference for the rest of the day. Zyromski, speaking in the name of the French Socialist Party, declared in the name of the whole Party its readiness to throw its whole weight behind action to get the foreign troops out of Spain, and to secure the possibility for the Spanish Government to exercise its international legal right to buy arms and other supplies it needed. The Spanish demands have been formulated in thé following points and presented to the Commission:- (1) Immediate publication of the document, explaining the character and significance of the Spanish war, publication of which was decided upon at the November meeting of the Internationals in Paris. (2) Recognition of the complete failure and breakdown of the Non-Intervention Committee. (3) Immediate resumption of the rights of the Spanish Government to buy arms and to import them and other needed products unhindered by the piracy at present being practised on the seas. (4) Immediate withdrawal of all foreign troops from Spain. (5) A vigorous protest against the employment of the Italian and German Fleets to control the Spanish Government's coasts. The Scandinavians have put in a resolution embodying the following three points:— (1) The present " non-intervention " policy has failed completely. (2) The new control scheme must be regarded as a last effort. (3) Should this effort fail and should we have in a few weeks evidence of failure then the policy must be entirely changed. PIETRO NENNI, who spoke in the name of the Italian delegation. Spanish delegates to the International Conference. From left to right: Pretel, Treasurer of the U.G.T.; Pedroso, Professor of Law at Seville University; Pasqual Tomas, Assistant General Secretary of the U.G.T.; Zabalza, Secretary of the Federation of Peasants. PUBLISH ! DEMAND that Bevin's speech to the International Labour Conference on Spain yesterday be published in full. DEMAND that Bevin's speech to the National Council of Labour on Tuesday be published in full. Let the British Labour movement know what their representatives are saying and doing in their name. End the secrecy ! Let the full shame of the British Labour chiefs' role be known in order that the mass of the Labour movement may fight and end it. 292/946/22/6(i)